An accelerometer-based guidance device for CT-guided procedures: an improved wireless prototype. Issue 6 (1st August 2022) - Pedersoli, Federico; Wilkmann, Christoph; Penzkofer, Tobias; Disselhorst-Klug, Catherine; Schmitz-Rode, Thomas; Kuhl, Christiane; Bruners, Philipp; Isfort, Peter
Abstract: Introduction: The aim of the study was to demonstrate the feasibility of a prototype for accelerometer-based guidance for percutaneous CT-guided punctures and compare it with free-hand punctures. Material and methods: The prototype enabled alignment with the CT coordinate system and a wireless connectivity. Its feasibility was tested in a swine cadaver model: 20 out-of-plane device-assisted punctures performed without intermittent control scans (one-step punctures) were evaluated regarding deviation to target and difference between planned and obtained angle. Thereafter, 22 device-assisted punctures were compared with 20 free-hand punctures regarding distance to target, deviation from the planned angle, number of control scans and procedure time. Differences were compared with the Mann–Whitney U-test ( p  < .05). Results: The one-step punctures revealed a deviation to target of 0.26 ± 0.37 cm (axial plane) and 0.21 ± 0.19 cm (sagittal plane) and differences between planned and performed puncture angles of 0.9 ± 1.09° (axial plane) and 1.15 ± 0.91° (sagittal planes). In the comparative study, device-assisted punctures showed a significantly higher accuracy, 0.20 ± 0.17 cm vs. 0.30 ± 0.21 cm ( p  < .05) and lower number of required control scans, 1.3 ± 1.1 vs. 3.7 ± 0.9 ( p  < .05) compared with free-hand punctures. Conclusion: The accelerometer-based device proved to be feasible and demonstrated significantly higher accuracy and required significantly less control scans compared to free-hand puncture.